Occurrence of Pandarus bicolor (Siphonostomatoida: Pandaridae) on vulnerable shark species: Oxynotus centrina and Squalus acanthias from turkish marine waters. - Oktener, A., D. Ventura & M. Sirin (Vie Et Milieu-Life And Environment, 2020)
The angular rough shark Oxynotus centrina (Squaliformes; Oxynotidae) and the picked dogfish Squalus acanthias (Squaliformes; Squalidae) are known as vulnerable deep-sea shark species by the International Union Conservation Nature (IUCN). Pandarus bicolor (Copepoda, Pandaridae) is reported for the first time on angular rough shark and picked dogfish from Turkish waters, during a demersal fish stock assessment in the Sea of Marmara. This parasitic copepod was found both on the body surface and fins of the hosts. Although this parasite is reported from several shark species, its occurrence has never been reported from the angular rough shark in the world. In this paper, morphological characters belonging to P. bicolor samples were assessed and described through photos and drawings.